THE REPRESENTATION OF CLASS STRUGGLE AS THE RESPONSE OF ALIENATION IN THE GREATES SHOWMAN (2017) FILM - Nurrahma, Virza Mei Utami; Valiantien, Nita Maya; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This research aims to describe the class struggle as the response of five variants alienation namely powerlessness, meaninglessness, normlessness, isolation and self-estrangement in The Greatest Showman film. This research also aims to reveal how the alienated characters did the class struggle because of the bad treatment and the unfair action they got then attempted to change their life condition and defend themselves. The data in this qualitative research are words, phrases, and sentences based on dialogues, narrations and monologues that indicated the alienation and class struggle in the film. The findings of this research showed that Barnum as the main character experienced alienation in the form of powerlessness, meaninglessness, normlessness and self-estrangement. Meanwhile, the other characters such as Barnum’s family and the circus members experienced powerlessness, meaninglessness and isolation. The characters of this film also did class struggle by two aspects which are economic and political. From the economic, the alienated people try to improve their living conditions to have a better life and more decent. From the political, the alienated people also struggle against the oppressor and defend their rights by fighting back the people who alienated them.